2019
DOI: 10.1111/1467-8489.12331
|View full text |Cite
|
Sign up to set email alerts
|

Canadian beef and dairy farmers’ attitudes towards animal vaccines

Abstract: The willingness to pay (WTP) approach is increasingly being used in different disciplines to assess peoples' readiness to accept change. This paper assesses the potential for two subunit vaccines for the prevention and control of bovine tuberculosis and paratuberculosis in cattle. A survey of beef and dairy farmers was conducted across Canada to identify factors that influence their WTP for subunit vaccines. Estimated results of the interval-data model indicate that the size of a farmer's cattle herd, neighbou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Farmers with many sheep and those who rely more heavily on sheep farming for their income might consider faecal testing and deworming more seriously than those with fewer sheep due to the economic importance of the decision (cf., e.g., Ugochukwu and Phillips (2019)). This is observed in our estimation, in which both factors are associated with more frequent faecal testing.…”
Section: Discussion a N D Conc Lusionsmentioning
confidence: 99%
“…Farmers with many sheep and those who rely more heavily on sheep farming for their income might consider faecal testing and deworming more seriously than those with fewer sheep due to the economic importance of the decision (cf., e.g., Ugochukwu and Phillips (2019)). This is observed in our estimation, in which both factors are associated with more frequent faecal testing.…”
Section: Discussion a N D Conc Lusionsmentioning
confidence: 99%
“…27 That private veterinary surgeons and other suitably qualified persons (i.e., veterinary technicians) were seen as the 'easiest' option for administering Cat-tleBCG vaccine was unsurprising; veterinarians are routinely advising on the use of and dispensing vaccines. In addition, farmers see their own veterinarians as their most important source of information surrounding vaccination, 28 and they are generally trusted by the farming community. 29,30 Whether vaccine doses would be offered to farmers free of charge was key for affecting how attractive uptake was.…”
Section: Discussionmentioning
confidence: 99%
“…It was unsurprising that farmers were unwilling to pay directly for vaccine doses under a mandatory deployment mechanism; in many jurisdictions, including the UK, mandatory vaccination costs are typically paid for by the government. 28 Research in Canada found that herd size, social acceptability and buyer recommendations had a strong influence on whether farmers would pay for livestock vaccinations. 28 Here, we found that previous encounters with bTB had a strong effect on how unattractive paying towards doses was.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations